The Relationship Between Social Support and Subjective Well Being in Early College Students at Bandung Islamic University - Kamilah, Nadiefa; Budiman, Agus (Bandung Conference Series: Psychology Science, 2024)
Abstract. Early college students are faced with changes such as moving to a higher education structure, a new learning system, and interaction with a wider environment. Early college students are also in the transition from late adolescence to early adulthood. The changes that occur in these students cause various feelings ranging from happy, sad to lonely, this can be a threat to students because subjective well being helps them to perform well. Subjective well being is related to social support, where with social support students are expected to have good subjective well being. The problems in this study are: (1) How’s the description of subjective well being in early level students at faculty of psychology UNISBA? (2) How’s the description of social support in early level students at faculty of psychology UNISBA? (3) How’s the level of relationship between social support and subjective well being in early level students at UNISBA?. The research design uses a quantitative method approach with a correlational type.The population in this study were early semester active students at the faculty of psychology UNISBA with 70 active students in 2nd semester as the sample, with simple random sampling technique. Data collection techniques used were questionnaires and observations. Data analysis technique used is simple regression analysis technique. The results of this study are: there is a positive relationship between social support and subjective well being. There are 31% of students have a high level of social support and subjective well being. Abstrak. Mahasiswa tingkat awal dihadapkan pada perubahan seperti perpindahan ke struktur pendidikan yang lebih tinggi, sistem pendidikan yang baru, hingga interaksi lingkungan yang lebih luas. Mahasiswa tingkat awal juga berada pada masa transisi dari remaja akhir menuju dewasa awal. Adanya perubahan pada mahasiswa ini bisa menimbulkan berbagai perasaan dari mulai bahagia, sedih hingga kesepian. Hal ini dapat menjadi ancaman bagi subjective well being mahasiswa karena subjective well being membantu untuk berprestasi dengan baik. Subjective well being berkaitan dengan dukungan sosial. Adanya dukungan sosial mahasiswa diharapkan memiliki subjective well being yang baik. Berdasarkan hal tersebut, maka permasalahan dalam penelitian ini adalah (1) Bagaimana gambaran subjective well being pada mahasiswa tingkat awal di fakultas psikologi UNISBA? (2)Bagaimana gambaran dukungan sosial pada mahasiswa tingkat awal di fakultas psikologi UNISBA? (3)Bagaimana tingkat hubungan antara dukungan sosial dengan subjective well being pada mahasiswa tingkat awal di UNISBA?. Desain penelitian menggunakan pendekatan metode kuantitatif dengan jenis korelasional. Populasi penelitian merupakan mahasiswa aktif fakultas psikologi semester awal di UNISBA dengan 70 orang mahasiswa aktif semester 2 sebagai sampelnya, menggunakan teknik sampel simple random sampling. Teknik pengumpulan data yang digunakan adalah kuesioner dan observasi. Teknik analisis data yang digunakan adalah analisis regresi sederhana. Hasil dari penelitian ini adalah: terdapat hubungan positif antara social support dengan subjective well being. Sebanyak 31% mahasiswa memiliki tingkat social support dan tingkat subjective well being yang tinggi.